2007
DOI: 10.1111/j.1475-4762.2007.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuity and change: (re)constructing environmental geographies in late Soviet and post‐Soviet Russia

Abstract: Environmental studies conducted worldwide often overlook the knowledge traditions of the locales where they are conducted. Addressing this issue, I investigated the geographic journal literature of late Soviet (1980Soviet ( -1989 and post-Soviet (1990post-Soviet ( -2003 Russia. Notable trends are increasing criticism of environmental and resource management in Russia and a (re)turn to pre-socialist Russian theorizations of society-nature interactions. Specifically, the noösphere, ethnogenesis and geosystems ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 30 publications
0
10
1
Order By: Relevance
“…Keeping a foot in both camps help minimize these various risks, Kuklina found. Her work contrasts with earlier authors, such as Jessica Graybill, who found that, after the collapse of the Soviet Union, indigenous groups relied more heavily on local knowledge and the fruits of the land than they had before 1991 (Graybill 2007, Wilson Rowe 2008.…”
Section: Indigenous Issuescontrasting
confidence: 50%
“…Keeping a foot in both camps help minimize these various risks, Kuklina found. Her work contrasts with earlier authors, such as Jessica Graybill, who found that, after the collapse of the Soviet Union, indigenous groups relied more heavily on local knowledge and the fruits of the land than they had before 1991 (Graybill 2007, Wilson Rowe 2008.…”
Section: Indigenous Issuescontrasting
confidence: 50%
“…This extract illustrates the value of requiring citizens to be responsible for their immediate surroundings (Blum, ; Dobson, ; Gooch, ; Oldfield and Shaw, ). As Graybill (, p. 17) argues, ‘effective management of environmental problems’ requires an understanding of ‘locally produced knowledge and values’. However, such a parochial and confined approach to environmental management was criticized, that people ‘live in their ‘small world” (regulator B), unaware of environmental damage beyond their immediate surroundings.…”
Section: Resultsmentioning
confidence: 99%
“…indeed, the actors involved showed high levels of capacity with regard to local knowledge and often tailored their decisions towards actions which did not require large amounts of funding (Graybill 2007).…”
Section: …And the Russian Approachmentioning
confidence: 99%
“…More importantly, there was a move towards private initiative, as the “diminishing power of the environmental state” meant that environmental protection shifted to newly forming coalitions of firms and environmental NGOs in various regions, setting standards and demanding region-specific environmental improvement ( Aksenova and Nedelkov 2002 ). Despite a lack of funding or capacity (in its traditional sense, that is, well-trained staff and infrastructure), these initiatives continued to experiment with polycentric forms of decision-making; indeed, the actors involved showed high levels of capacity with regard to local knowledge and often tailored their decisions towards actions which did not require large amounts of funding ( Graybill 2007 ).…”
Section: …And the Russian Approachmentioning
confidence: 99%